2006
DOI: 10.26421/qic6.2-3
|View full text |Cite
|
Sign up to set email alerts
|

The computational power of the W and GHZ states

Abstract: It is well understood that the use of quantum entanglement significantly enhances the computational power of systems. Much of the attention has focused on Bell states and their multipartite generalizations. However, in the multipartite case it is known that there are several inequivalent classes of states, such as those represented by the W-state and the GHZ-state. Our main contribution is a demonstration of the special computational power of these states in the context of paradigmatic problems from classical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 14 publications
0
65
0
Order By: Relevance
“…11|) is a separable state. On the other hand, W states still retain a considerable amount of entanglement after the removal of an arbitrary particle, and it has been shown that the n-qubit W state is the optimal state for leader election [24]. This shows that the entanglement of GHZ and W states is of a different nature, and such qualitative aspects of entanglement and their characterisation will be investigated in the next section.…”
Section: Bipartite and Multipartite Systemsmentioning
confidence: 95%
See 1 more Smart Citation
“…11|) is a separable state. On the other hand, W states still retain a considerable amount of entanglement after the removal of an arbitrary particle, and it has been shown that the n-qubit W state is the optimal state for leader election [24]. This shows that the entanglement of GHZ and W states is of a different nature, and such qualitative aspects of entanglement and their characterisation will be investigated in the next section.…”
Section: Bipartite and Multipartite Systemsmentioning
confidence: 95%
“…Returning to the concept of symmetry in physics, we recall that permutation-symmetric quantum states appear naturally in some systems [22,23], that it is possible to prepare them experimentally [3][4][5][6], and that they have found some applications [24][25][26][27]. Many canonical states that appear in quantum information science are symmetric, e.g.…”
Section: Motivationmentioning
confidence: 99%
“…that will disconnect the other two with certainty [BR01]. This enables the state | W to support protocols for which | GHZ is inadequate, see for example [DP06].…”
Section: The Entanglement Classification Problemmentioning
confidence: 99%
“…While quantum communication often relies on entanglement distribution between two end-nodes, there are a several possible applications that go beyond the two-party paradigm and require multipartite entanglement, which has no classical analogue. Important examples of these applications are quantum sensor networks [7][8][9][10], multi-party quantum communication [11][12][13] and computation [14,15].…”
Section: Introductionmentioning
confidence: 99%